First record of Ripartitella brasiliensis (Fungi, Agaricales) in Mexico - Guzmán-Dávalos, Laura; Guzmán, Gastón (Instituto de Ecología, A.C., 1988)
The tropical fungus Ripartitella brasiliensis (Speg.) Sing. is described for the first time from the Mexican mycoflora. It was found in Manantlán Mountains, in the State of Jalisco.